Exposure dating of precariously balanced rocks - Balco,G; Purvance,MD; Rood,DH (Quaternary Geochronology, 2011)
Precariously balanced rocks (PBRs) are freestanding boulders that are precarious or fragile in the sense that they could be toppled by relatively low-amplitude earthquake ground motion. They are important in paleoseismology because their continued existence limits the amplitude of ground motion experienced at their location during their lifetime. In order to make quantitative use of PBRs for seismic hazard studies, one must determine when they attained their present state of fragility, that is, the point in time when the contact between the rocks and the pedestals on which they rest was exhumed from surrounding soil and the rock became vulnerable to earthquake ground motions. Cosmogenic-nuclide exposure dating can be used for this purpose, but is complicated because nuclide production occurs throughout exhumation of the PBR, so the apparent exposure age of any part of the rock surface exceeds the time that the rock has actually been precariously balanced. Here we describe a method for determining the length of time that a PBR has been fragile by measuring cosmogenic-nuclide concentrations at several locations on the PBR surface, and linking them together with a forward model that accounts for nuclide production before, during, and after exhumation of the PBR. Fitting model to data yields the rate and timing of rock exhumation and thus the length of time the rock has been fragile. We use this method to show that an example PBR in southern California has been fragile for 18.7 ± 2.8 ka. © 2011 Elsevier B.V.